2019
DOI: 10.3390/ma12193184
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties of a Novel Zirconium Phosphate-Glycinediphosphonate Loaded with Either Zinc or Silver

Abstract: A novel compound consisting of a zirconium phosphate-glycinediphosphonate (ZPGly) has recently been introduced. This 2D-structured material forming nanosheets was exfoliated under appropriate conditions, producing colloidal aqueous dispersions (ZPGly-e) which were then loaded with zinc (Zn/ZPGly) or silver ions. Silver ions were subsequently reduced to produce metallic silver nanoparticles on exfoliated ZPGly nanosheets (Ag@ZPGly). In the search for new anti-infective materials, the present study investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…104,105 Even though band gap of Zr is around 5.0 eV, due to its strong similarity in its isovalent state with Ti 4+ such that electronegativity of Zr 4+ (1.40) is comparable with that of Ti 4+ (1.54), absorption edge shis to visible region with a presumable reduction in band gap (see Table 1) caused by either defects produced by trace concentration of Zr 4+ in TiO 2 lattice or by reduced crystal domains. 58,92,94,106 An obvious change in optical absorbance of nanomaterials as a function of crystallite size may occur due to quantum connement effects. 91 This variation in optical properties (redshi in wavelength) is considered a primary prerequisite for the enhancement of photocatalytic behavior of nanoparticles.…”
Section: Materials Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…104,105 Even though band gap of Zr is around 5.0 eV, due to its strong similarity in its isovalent state with Ti 4+ such that electronegativity of Zr 4+ (1.40) is comparable with that of Ti 4+ (1.54), absorption edge shis to visible region with a presumable reduction in band gap (see Table 1) caused by either defects produced by trace concentration of Zr 4+ in TiO 2 lattice or by reduced crystal domains. 58,92,94,106 An obvious change in optical absorbance of nanomaterials as a function of crystallite size may occur due to quantum connement effects. 91 This variation in optical properties (redshi in wavelength) is considered a primary prerequisite for the enhancement of photocatalytic behavior of nanoparticles.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…55,56 Certainly, in some studies, these materials have also shown high effectiveness at reducing the feasibility of adherent bacterial species such as E. coli, Methicillin-resistant Staphylococcus aureus (MRSA), Bacillus subtilis, S. aureus, and Pseudomonas and therefore have been extensively used in biomedical applications. [57][58][59][60] In the current research work, we aimed to synthesize TiO 2 nanoparticles doped with various concentrations (2,4,6, and 8 wt%) of Zr through sol-gel method. The synthesized products were employed as photocatalysts to treat industrial wastewater and remove synthetic dye (Methylene blue).…”
Section: Introductionmentioning
confidence: 99%
“…ZrP has been successfully exfoliated and its nanosheets used for different applications [ 6 , 21 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The most widely used strategy for ZrP exfoliation consists of the intercalation of small amine cations that can easily displace the protons from the phosphate groups in an acid-base reaction and enter the interlayer space [ 51 ].…”
Section: Synthesis and Preparation Of Zrp Nanomaterialsmentioning
confidence: 99%
“…Metallic nanoparticles (MNPs) have also proven to be effective in controlling oral infections when coated on or incorporated into various materials [ 24 , 25 , 26 ]. They have been proposed as promising alternatives to traditional antimicrobial agents [ 27 , 28 , 29 ]. Silver (Ag), copper (Cu), and zinc (Zn) MNPs have received the most attention for their antimicrobial properties [ 24 , 25 , 26 , 27 , 30 ].…”
Section: Introductionmentioning
confidence: 99%